Fetal Anemia in Northern Thailand: Etiologies and Outcomes - Ratarat, Chitsanupong; Natesirinilkul, Rungrote; Sathitsamitphong, Lalita; Choed-Amphai, Chane; Fanhchaksai, Kanda; Charoenkwan, Pimlak; Tongsong, Theera (Biomedical Sciences and Clinical Medicine, 2024)
OBJECTIVE In Southeast Asia, hemoglobin (Hb) Bart’s disease is the primary cause of fetal anemia, although other causes are increasingly being identified. This study aimed to characterize the etiologies and outcomes of fetal anemia in northern Thailand. METHODS A retrospective chart review was conducted, involving pregnant women who attended antenatal care at Chiang Mai University Hospital between 2014 and 2021 and had a diagnosis by ultrasound findings of fetal anemia, or a fetal diagnosis of Hb Bart’s disease or other known hereditary anemias. RESULTS Among 71 fetuses from 64 pregnancies, 45 (63.4%) had Hb Bart’s disease. Twelve cases (16.9%) of fetal anemia were from other causes, including three cases of homozygous Hb Constant Spring, three cases of hereditary pyropoikilocytosis, one case of suspected red cell membrane disorder, one case each of Rh(D) alloimmunization, Hb H/Hb Pakse disease, transient abnormal myelopoiesis, syphilis infection, and one of unknown cause. All of the seven sets of twins (19.7%) had twin-to-twin transfusion syndrome (TTTS). Intrauterine transfusion was given in four cases of fetal hemolytic anemia which rendered good outcomes. Overall, 12 cases (16.9%) survived beyond the neonatal period. CONCLUSIONS Hb Bart’s disease remains the leading cause of fetal anemia in northern Thailand. Increasingly, frequently diagnosed causes include hemoglobinopathies and red cell membrane disorders.